Drought-tolerance of transgenic winter wheat with partial suppression of the proline dehydrogenase gene - Dubrovna, O. V.; Priadkina, G. O.; Mykhalska, S. I.; Komisarenko, A. G. (Regulatory Mechanisms in Biosystems, 2022)
The global climate changes and the consequent increase in the number of soil and air droughts during the vegetation period of grain crops require the development of new strategies to adapt plants to those yield-decreasing stressors. A relevant way of increasing drought-tolerance of cereals is the use of biotechnological methods, particularly RNA interference, which can down-regulate the activity of plants’ genes and increase concentration of stress metabolites that perform osmoprotective functions during drought. We studied the tolerance to soil moisture shortage in transgenic plants of winter wheat with partial suppression of the proline dehydrogenase gene, obtained using the technology of short interfering RNAs. We analyzed physiological and biochemical parameters and structural elements of yield productivity of 4 wild genotypes and their transgenic lines with reduced activity of proline dehydrogenase in the conditions of 7-day drought during the late booting–ear emergence. We determined that the presence of double-stranded RNA suppressor of the proline dehydrogenase gene in transgenic lines led to increase in the level of accumulation of free proline in flag leaves. At the same time, its concentration in transgenic lines was higher than in untransformed plants of the wild genotypes in both drought conditions and conditions of sufficient moisture. We found that against the background of water deficiency, the total chlorophyll content in leaves of plants of transgenic lines was significantly higher, and the ratio of carotenoids to chlorophyll was lower than in plants of the wild genotypes, suggesting mitigation of the negative impact of drought on the plants of transgenic lines. Lacking soil moisture, genetically altered lines of wheat had significantly higher parameters of the structure of grain yield compared with untransformed genotypes. At the same time, we observed genotypic difference according to grain productivity in biotechnological plants. Therefore, the results we obtained confirm the perspectives of using the technology of short interfering RNAs to increase tolerance of winter wheat to water deficiency.